Dynamics of self-propelled particles passing a bottleneck - Mahdieh Mohammadi; Kirsten Harth; Dmitry Puzyrev; Tina Hanselka; Torsten Trittel; Ralf Stannarius (New Journal of Physics, 2020)
We study the passage of active and passive granular particles through a bottleneck under gravitational bias. The grains are pharmaceutical capsules with spherocylindrical shapes on a vibrating table. The vibrating ground plate is slightly tilted in order to break the in-plane symmetry and to give particles a motivation to move in a preferential direction. The passage through a narrow gate with openings comparable to the grain length is studied using video imaging. Particle positions and velocities are extracted from the recorded frames. We find striking differences between the behaviour of asymmetric, active capsules and symmetric, passive ones. The active grains show an astonishingly strong dependence of the passage rates on the gate width, while for passive grains, this dependence is linear as expected. The cumulative distributions of delays between subsequent particles passing the outlet, a key parameter in egress studies, also differ substantially between active and passive grains. Tilt angle and excitation parameters have only little influence on the observed dynamic features, they merely rescale time.